Preschool Language Interventions for Latino Dual Language Learners with Language Disorders: What, in What Language, and How - Simon-Cereijido, Gabriela (Seminars in Speech and Language, 2015)
About a quarter of young children in the United States are dual language learners. The large majority are Latino children who are exposed to Spanish in their homes. The language needs of Latino dual language preschoolers are different from the needs of monolingual English-speaking children. As a group, they are likely to live in environments that put them at risk of delays in language development. This situation is direr for dual language preschoolers with language impairment. Recent findings from studies on interventions for Spanish–English preschoolers with language impairment suggest that a bilingual approach does not delay English vocabulary and oral language learning and promotes Spanish maintenance. Targets and strategies for different language domains are described. The effects of pullout versus push-in interventions for this population are preliminarily explored.
Keywords: Dual language learners; language disorders; intervention